Práticas Integrativas e Complementares e Educação Permanente em Saúde: implicação na Atenção Primária à Saúde de Minas Gerais - Heloisa Helena Monteiro Braga (2019)
Introduction: The Integrative and Complementary Practices (PIC) are therapeutic resources that offer new perspectives for an individual reagarding his health care in a holistic view. Even though most of the health care professionals believe in the importance of the PIC for their jobs and for the Sistema Único de Saúde (SUS), there are many factors that can make it harder to make the PIC work in the health care environment. One of the obstacles is the failure in teaching and educating professionals, the opposition regarding the new model of care and the lack of awareness from the employees, political and technical, to use the PIC inside their jobs and SUS. To provide a better education and effective use of the PIC, it was developed in Minas Gerais, duo to a partnership between Escola de Saúde Pública (ESP) and Secretaria de Estado de Saúde (SES), an educational study, developed between 2013 and 2014, for directors, professionals and health counselors named Workshop on Popular Education in Health for Supporters of the State Policy on Integrative and Complementary Practices, in this study named Educational Intervention PEPIC SES/MG. Objective: Analyze the development of PIC in Primary Health Care, as well as the production in other health senses, through the participants in this study. Methodology: It is an exploratory study, descritive with qualitative view done with twenty five health professionals from forty counties from the educational area. The methodology in this study was divided in four parts: scenario definition, participant characterization, data collection and analysis. The scenario used was the place of work for the participants professionals. The data was colected through the semi-structured interview technique. To analyze the data, Bardins Content Analysis Theory was used. Results: There were formed categories based on the interviewees answers to the survey, which were: development of the PIC, changes in the health enviroment of the countie, production of meanings for health. The results shows that the participation of the health professionals in this study brought wisdom and new techniques for the development of the PIC. Overall, the PIC was put in action in the counties studied, even though some professionals had some problems with it, due to lack of support from their bosses. For the development of the PIC in location the professionals used different strategies as elaboration and implementation of projects for the implementation of PIC, dissemination of practical modalities for other professionals and institutionalization of PIC through the creation of Municipal Policy. Also, it was noted changes in the way the professionals used to work before using PIC. From the new patterns of work created after using PIC, the adoption of a new paradigm of health, understanding of the possibility of differential care and openness to new ways of experiencing health are some that standout. Conclusion: the objects of the study were reached. It is important to say that the incorporation of knowledge and learning related to public policies of PIC has provided encounters and experiences with powerful PIC to generate the production of concepts and new modes of subjectivation. Therefore, this knowledge is believed to be a potential transformative of health care practices.